Relationship between balance ability, training and sports injury risk - Hrysomallis, C. (Sports Medicine, 2016)
Traditionally, balance training has been used as part of the rehabilitation programme for ankle injuries. More recently, balance training has been adopted to try and prevent injuries to the ankle and knee joints during sport. The purpose of this review is to synthesise current knowledge in the area of balance ability, training and injury risk, highlight the findings and identify any future research needs. A number of studies have found that poor balance ability is significantly related to an increased risk of ankle injuries in different activities. This relationship appears to be more common in males than females.